Opioid use in the acute setting: A survey of providers at an academic medical center - Oyler, PharmD, Douglas R.; Deep, MD, Kristy S.; Chang, MD, Phillip K. (Journal of Opioid Management, 2018)
Objective: To examine attitudes, beliefs, and influencing factors of inpatient healthcare providers regarding prescription of opioid analgesics. Design: Electronic cross-sectional survey. Setting: Academic medical center. Participants: Physicians, advanced practice providers, and pharmacists from a single academic medical center in the southeast United States. Main Outcome Measures: Respondents completed survey items addressing: (1) their practice demographics, (2) their opinions regarding overall use, safety, and efficacy of opioids compared to other analgesics, (3) specific clinical scenarios, (4) main pressures to prescribe opioids, and (5) confidence/comfort prescribing opioids or nonopioids in select situations. Results: The majority of the sample (n = 363) were physicians (60.4 percent), with 69.4 percent of physicians being attendings. Most respondents believed that opioids were overused at our institution (61.7 percent); nearly half thought opioids had similar efficacy to other analgesics (44.1 percent), and almost all believed opioids were more dangerous than other analgesics (88.1 percent). Many respondents indicated that they would modify a chronic regimen for a high-risk patient, and use of nonopioids in specific scenarios was high. However, this use was often in combination with opioids. Respondents identified patients (64 percent) and staff (43.1 percent) as the most significant sources of pressure to prescribe opioids during an admission; the most common sources of pressure to prescribe opioids on discharge were to facilitate discharge (44.8 percent) and to reduce follow-up requests, calls, or visits (36.3 percent). Resident physicians appear to experience more pressure to prescribe opioids than other providers. Managing pain in patients with substance use disorders and effectively using nonopioid analgesics were the most common educational needs identified by respondents. Conclusion: Most individuals believe opioid analgesics are overused in our specific setting, commonly to satisfy patient requests. In general, providers feel uncomfortable prescribing nonopioid analgesics to patients.